Antifungal Activity on Botrytis fabae and Response of Agronomic Variables of Plant Extracts in Faba Beans - Guadalupe Mora-Baez; Lucia Torres-Rueda; Antonio Morgado-Gonzalez; Cristian Nava-Díaz; Ramón Marcos Soto-Hernández; Luis Manuel Carrillo-López (Microbiology Research)
Chocolate spot (Botrytis fabae) is a disease that threatens faba bean production in Mexico, as it can cause up to 70% yield losses. Currently, indiscriminate fungicides combat this disease, leading to environmental and human health problems. In this context, the effect of applying ethanolic extracts of two native plants of Mexico (Litsea glaucescens and Tagetes erecta), and Ruta graveolens was evaluated under in vitro and field conditions, in comparison to a commercial fungicide (Benomyl®) on the percentage of inhibition, incidence, severity, and relevant agronomic variables (plant height, number of secondary stems, number of flowers, and number and weight of pods). Applications with ethyl alcohol and water were used as controls. Both the bay laurel extract and Benomyl® achieved 100% inhibition under in vitro conditions, while in the field, they reduced severity by up to 51% at the beginning and end of the experiment. Plants treated with the marigold extract showed greater plant height (90.3 cm), while those treated with ethyl alcohol (control 1) had the lowest height (76.5 cm). The fungicide and bay laurel extract produced pods with higher weight (166.3 g and 139.2 g, respectively), while the water control produced pods weighing only 33.1 g. The ethanolic extract of bay laurel could potentially replace the chemical control of chocolate spot without affecting faba bean crop yield.